All the colors of the world: biotic homogenization-differentiation dynamics of freshwater fish communities on demand of the Brazilian aquarium trade - Magalhães, André L. B.; Daga, Vanessa S.; Bezerra, Luis A. V.; Vitule, Jean R. S.; Jacobi, Claudia M.; Silva, Luiz G. M. (Hydrobiologia, 2020)
Non-native freshwater fish introduced via the aquarium trade can cause major changes at the community level over time and space, resulting in dynamics context dependencies within homogenization process. We investigated fish biodiversity in anthropogenically impacted headwater creeks (i.e., under elevated propagule pressure) located in southeastern Brazil, through a standardized sampling program. We assessed ichthyological community composition with the aim of quantifying spatio-temporal dynamics across creeks. We divided the sampling period according to decades, in which “2000s” represented 2003, 2004, 2005, and 2006, while “2010s” represented 2015. Changes in pairwise community similarity indicated biotic homogenization in the 2000s (i.e., communities became more similar over time). In contrast, changes in pairwise similarity in the 2010s indicated biotic differentiation. We suggest that these changes are caused by the extirpation of both native and non-native species due to environmental degradation and the occurrence of six new non-native species. The beta-diversity increased between sampling seasons and creeks across decades, also indicating biotic differentiation. Our study provides strong evidence for a transition phase from biotic homogenization to differentiation of fish communities over time, caused by interaction between older environmental degradation and more recent impacts from the Brazilian aquarium trade, reinforcing the importance of simple, practical, and inexpensive long-term studies to understand biodiversity-related processes.